RANCANG BANGUN APLIKASI SISTEM INFORMASI GEOGRAFIS (SIG) PENCARIAN MASJID TERDEKAT BERBASIS ANDROID DI KOTA SEMARANG DENGAN METODE GEOLOCATION DAN HAVERSINE FORMULA - hidayat, dwiki krisma; Harjanta, Aris Tri Jaka (Jurnal Transformatika, 2019)
Prayer is one of the worship that must be done by all Muslims in this world. If you have entered prayer time, whether we are wherever we are as a devout Muslim it is obligatory to immediately do the prayer. No exception when we are visiting or traveling in a certain area. Therefore, it will be very helpful if there is an application that can find the location of the nearest mosque that can be accessed using a smartphone. Previously, there were similar applications but only accessible via the web. Then, using google maps actually can already find the closest mosque, but there are still shortcomings, namely location data displayed at some point is invalid (the location at certain points there is no mosque). So, the Sigoca Master application (Nearest Mosque Search Information System) in Semarang City based on Android is made to help all Muslims who are visiting or traveling in the City of Semarang. Geolocation and Haversine Formula are the methods I will use to build the Sigoca Master application. With these methods, it is expected that the application built can help find the location of the nearest mosque from the user's location.
Keywords: Android; Mosque; Geolocation; Haversine Formula